Heavy metal contamination of clarias gariepinus from a lake and fish farm in Ibadan, Nigeria (2004)
Adult Clarias gariepinus (African Catfish) were purchased from Eleiyele Lake and Zartech fish farm in Ibadan. Water samples were also collected in February (dry season) and June (rainy season), 2002. Gill, bone, intestine, muscle and water samples were analyzed for five metals: manganese, copper, zinc, iron, and chromium by atomic absorption spectroscopy (AAS) in two separate experiments. In each case, two tissues were compared with the levels of the metals in water viz: Gill, bone, and water; intestine, muscle and water. Generally, lower concentrations of the metals were recorded in water than fish tissues. Higher concentrations of zinc than recommended by the Federal Environmental Protection Agency were recorded in the fish during the dry season. Iron was the dominant metal in the muscle while Chromium was the least. Significant differences (p<0.05) were recorded in copper and zinc concentrations in the muscle, intestine and water during the dry and rainy seasons .In gill, bones and water, significant differences (p<0.05) were only recorded for the two stations for copper during the rainy season and only zinc was significantly different (p<0.05) in the dry season. It was concluded that though the heavy metals of interest were present in measurable quantities there were still within safe limits for consumption